The Correlation between Slow Coronary Flow and Galectin-3 - Kobat, Mehmet Ali; Kalayci, Mehmet (Cardiology and Cardiovascular Medicine, 2021)
Background: It was investigated whether Galectin-3 is one of the contributing factors to slow coronary flow (SCF). In the cases with SCF angiography shows lagged opacification of epicardial coronary arteries. Research has reported that several determinants of SCF are inflammation and endothelial dysfunction. It is a new finding that Galactin-3 also causes intravascular inflammation followed by lipid endocytosis, macrophage activation, cellular proliferation, monocyte chemotaxis, and cell adhesion, successively. Thus, the cases enrolled in this study were selected based on their angiographical negative results with obstructive coronary artery disease. Method: The study group consists of 94 patients with SCF, and the control group of 92 with normal coronary flow (NCF). The total (n=186) were the cases who were examined for diagnosis of coronary artery disease based on coronary angiography records and atherosclerotic lesion was not detected. SCF rates were identified using TIMI frame count (TFC). Results: The groups had similar demographic characteristics at the baseline. The study group had significantly higher values (2.4 ± 0.6 mg/dL and 16.6 ± 0,7 ng/mL) than the control group (1.1 ± 0.2 mg/dL and 9.2 ± 0,6 ng/mL) in terms of average serum high sensitivity C-reactive protein (hsCRP) (p=.005) and Galectin-3 (p=.003), respectively. For diagnostic purpose at a 95% confidence interval, the plasma Galectin-3 levels were moderate to distinguish the SCF with the NCF patients (0.7220.722 Conclusion: It was determined that serum Galectin-3 levels were significantly higher in the SCF patients. It may be too early to reach a conclusion related to the underlying pathological process of SCF. Thus, the present study could stimulate further studies on coronary vasculature to discover more active roles of Galectin-3 in the SCF p